1995
DOI: 10.1021/jo00131a018
|View full text |Cite
|
Sign up to set email alerts
|

Oxone Oxidation of Selenides: A Mild and Efficient Method for the Preparation of Selenones

Abstract: Selenide (a) to selenoxide (b) or selenone (c) oxidation is a useful operation in organic synthesis, and a variety of reagents have been developed for this purpose. a b C Most investigations have focused on the preparation and reactivity of selenoxides,' but selenones have received little attention. Selenones have been prepared by oxidation of selenides using an excess of peroxycarboxylic acids,2 potassium permanganate,2 or hydrogen peroxide in the presence of seleninic acid.3 These methods have several disadv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 1 publication
2
29
0
Order By: Relevance
“…Despite the aryl-aryl biaryl compounds, researchers have moved towards organoselenium compounds because of their biological importance [93][94][95]. Often, diaryl selenide and its derivatives have shown their great antioxidative properties [96].…”
Section: Miscellaneous Arylationmentioning
confidence: 99%
“…Despite the aryl-aryl biaryl compounds, researchers have moved towards organoselenium compounds because of their biological importance [93][94][95]. Often, diaryl selenide and its derivatives have shown their great antioxidative properties [96].…”
Section: Miscellaneous Arylationmentioning
confidence: 99%
“…363 Treatment of tetraaryl-substituted selenophenes with DMDO (2 equivalents) in acetone at 0 1C leads to the clean formation of the selenophene-1,1-dioxides in good-to-high yield. 364 The isolation of the corresponding selenoxides when using 1 equivalent of DMDO was unfruitful as these compounds are labile, except in the case of benzo [b]selenophene.…”
Section: Oxidation Of Selenides and Selenoxides To Selenonesmentioning
confidence: 99%
“…This method was applied to prepare tricarbonyl compounds. Selenides were oxidized with Oxone in buffered methanol to the corresponding selenones in quantitative yields 169 . Webb and Levy showed that several boronic acids and boronic esters can be converted into the corresponding alcohols in excellent yields (equation 60).…”
Section: E Potassium Peroxymonosulfatementioning
confidence: 99%